Preparation of Porous F-WO3/TiO2 Films with Visible-Light Photocatalytic Activity by Microarc Oxidation - Chung-Wei Yeh; Kee-Rong Wu; Chung-Hsuang Hung; Hao-Cheng Chang; Chuan-Jen Hsu (International Journal of Photoenergy)
Porous F-WO3/TiO2 (mTiO2) films are prepared on titanium sheet substrates using microarc oxidation (MAO) technique. The X-ray diffraction patterns show that visible-light (Vis) enabling mTiO2 films with a very high content of anatase TiO2 and high loading of WO3 are successfully synthesized at a low applied voltage of 300 V using electrolyte contenting NaF and Na2WO4 without subsequent heat treatment. The cross-sectional transmission electron microscopy micrograph reveals that the mTiO2 films feature porous networks connected by many micron pores. The diffused reflection spectrum displays broad absorbance across the UV-Vis regions and a significant red shift in the band gap energy (∼2.23 eV) for the mTiO2 film. Owing to the high specific surface area from the porous microstructure, the mTiO2 film shows a 61% and 50% rate increase in the photocatalytic dye degradation, as compared with the N,C-codoped TiO2 films under UV and Vis irradiation, respectively.